Current status and future perspectives of HLA-edited induced pluripotent stem cells - Koga, Keiko (Inflamm Regen, 2020)
In 2007, Human-induced pluripotent stem cells (iPSCs) were generated by transducing four genes (Oct3/4, Sox2, Klf4, c-Myc). Because iPSCs can differentiate into any types of cells in the body and have fewer ethical issues compared to embryonic stem (ES) cells, application of iPSCs for regenerative medicine has been actively examined. In fact, iPSCs have already been used for clinical applications, but at present, only autologous iPSC-derived grafts or HLA homozygous iPSC-derived grafts are being transplanted into patients following HLA matching. HLA is an important molecule that enables the immune system differentiates between self and non-self-components; thus, HLA mismatch is a major hurdle in the transplantation of iPSCs. To deliver inexpensive off-the-shelf iPSC-derived regenerative medicine products to more patients, it is necessary to generate universal iPSCs that can be transplanted regardless of the HLA haplotypes. The current strategy to generate universal iPSCs has two broad aims: deleting HLA expression and avoiding attacks from NK cells, which are caused by HLA deletion. Deletion of B2M and CIITA genes using the CRISPR/Cas9 system has been reported to suppress the expression of HLA class I and class II, respectively. Transduction of NK inhibitory ligands, such as HLA-E and CD47, has been used to avoid NK cell attacks. Most recently, the HLA-C retaining method has been used to generate semi-universal iPSCs. Twelve haplotypes of HLA-C retaining iPSCs can cover 95% of the global population. In future, studying which types of universal iPSCs are most effective for engraftment in various physiological conditions is necessary.